ABO incompatible living donor kidney transplantation in Korea: highly uniform protocols and good medium‐term outcome. (7th October 2013) - Kong, Jin Min; Ahn, Jeongmyung; Park, Jae Beom; Chung, Byung‐Ha; Yang, Jaeseok; Kim, Joong Kyung; Huh, Kyu Ha; Kim, Jong Man
Abstract The organ shortage is as serious in Korea as in other parts of the world. As about one‐third of the potential living donors are ABO incompatible (ABOi), transplantation across the blood group barrier can help overcome this shortage. One hundred and twenty‐five ABOi kidney transplantations (KTs) were performed between 2007 and 2010 in Korea. We collected the perioperative and follow‐up data for 118 of these patients until September 2011. The preconditioning and immunosuppressive protocols were almost identical across the different transplant centers, with rituximab but no splenectomy; pre‐transplant plasmapheresis (PP) with target anti‐A/B titer 8 or 16 on transplant day, on‐demand, rather than routine, post‐transplant PP, and tacrolimus‐based immunosuppressants. The number of patients and participating centers showed a rapid increase over time, and in 2010, ABOi KT (n = 79) comprised 10% of all the living donor KTs in Korea. The mean follow‐up period was 21 months (range, 1–56 months). Sixteen (14%) patients developed acute rejection, and three of these had antibody‐mediated rejection (AMR). Two‐yr patient and graft survival were 99.2% and 97.5%, respectively. No graft was lost due to AMR. ABOi KT is rapidly expanding in Korea with excellent medium‐term outcome and will help mitigate the organ shortage.